Stem Photosynthesis-A Key Element of Grass Pea (Lathyrus sativus L.) Acclimatisation to Salinity - Tokarz, Krzysztof M; Wesołowski, Wojciech; Tokarz, Barbara; Makowski, Wojciech; Wysocka, Anna; Jędrzejczyk, Roman J; Chrabaszcz, Karolina; Malek, Kamilla; Kostecka-Gugała, Anna (International journal of molecular sciences, 2021)
Grass pea (Lathyrus sativus) is a leguminous plant of outstanding tolerance to abiotic stress. The aim of the presented study was to describe the mechanism of grass pea (Lathyrus sativus L.) photosynthetic apparatus acclimatisation strategies to salinity stress. The seedlings were cultivated in a hydroponic system in media containing various concentrations of NaCl (0, 50, and 100 mM), imitating none, moderate, and severe salinity, respectively, for three weeks. In order to characterise the function and structure of the photosynthetic apparatus, Chl a fluorescence, gas exchange measurements, proteome analysis, and Fourier-transform infrared spectroscopy (FT-IR) analysis were done inter alia. Significant differences in the response of the leaf and stem photosynthetic apparatus to severe salt stress were observed. Leaves became the place of harmful ion (Na+) accumulation, and the efficiency of their carboxylation decreased sharply. In turn, in stems, the reconstruction of the photosynthetic apparatus (antenna and photosystem complexes) activated alternative electron transport pathways, leading to effective ATP synthesis, which is required for the efficient translocation of Na+ to leaves. These changes enabled efficient stem carboxylation and made them the main source of assimilates. The observed changes indicate the high plasticity of grass pea photosynthetic apparatus, providing an effective mechanism of tolerance to salinity stress.
Keywords: solný stres; Plant Development; stonky rostlin; Salt Stress; Seedlings; salt stress; photosynthetic apparatus; Salinity; ROS; Lathyrus sativus; cyclic electron transport; semenáček; vývoj rostlin; Photosynthesis; Stress, Physiological; photosystem II; fyziologický stres; Acclimatization; Lathyrus; linear electron transport; photosystem I; aklimatizace; Plant Stems; salinita; fotosyntéza